Steroid hormones as a non-lethal assessment of the reproductive biology in male and female blacktip reef sharks - Mourier, Johann; Planes, Serge; Mills, Suzanne C. (Frontiers in Fish Science, 2024)
Overexploitation of sharks and the destruction of their habitat has led to severe population declines and the need for conservation and management actions. Effective conservation management requires knowledge of the size at which a shark matures and an understanding of their breeding season, fundamental information to maintain appropriate population levels.Here we used reproductive endocrinology, oestrogen and androgen steroids, in combination with rare direct observations of mating, visual monitoring of reproductive status such as gestation and mating scars, as well as parentage analysis, to assess reproductive biology in male and female Chondrichthyans from the wild. Lengths at sexual maturity of female and male blacktip reef sharks corresponded closely with plasma 17β-estradiol, testosterone and 11-ketotestosterone measures respectively, but we found considerable variation in androgen levels for mature males. Size at sexual maturity of male and female blacktip reef shark deduced from direct or indirect evidence (mating scars or parentage assignment respectively), corresponded well with concentrations of androgen and oestrogen steroid hormones. We also identified that day length is the abiotic parameter that best determines the start of the breeding season. Endocrinology has brought additional important information to the reproductive biology and ecology of blacktip reef sharks.